Pembelajaran Berbasis Media Sosial: Peluang Dan Tantangan - Irfan (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to explore the opportunities and challenges in implementing social media-based learning. Using a literature review research method, this study examines various previous studies that discuss the use of social media in education, both in the context of student engagement, access to information, learning flexibility, and emerging challenges. The results of the study indicate that social media-based learning can increase student engagement, expand access to learning resources, and provide flexibility in the learning process. However, significant challenges were also found, such as distractions from non-educational content, teachers' unpreparedness in using technology, and privacy issues arising from the use of social media. This study makes an important contribution by identifying solutions that can be implemented, such as technology training for teachers and more structured arrangements for the use of social media.